Sistem Penunjang Keputusan Pemilihan Ketua UKM Bodhivijja dengan Menggunakan Metode Simple Additive Weighting (SAW) (Studi Kasus: STMIK Kharisma Makassar) - Marlina (STMIK KHARISMA Makassar, 2016)
Decision Support System in this study is in use by using simple additive weighting (SAW) is applied to the election of the chairman of the SME Bodhivijja , which is a student organization. SAW application of this by using five criteria: spirited leader , responsible , creative and innovative , honest and fair and have a good akedemik value . Defined 5 candidates for the chairman to be selected , and is calculated based on the SAW method . The results obtained by a chairman who has the highest score .